A Review on Emerging Pollutants in the Water Environment: Existences, Health Effects and Treatment Processes - Arman, Nor Zaiha; Salmiati, Salmiati; Aris, Azmi; Salim, Mohd Razman; Nazifa, Tasnia Hassan; Muhamad, Mimi Suliza; Marpongahtun, Marpongahtun (Water (Basel), 2021)
Emerging pollutants (EPs), also known as micropollutants, have been a major issue for the global population in recent years as a result of the potential threats they bring to the environment and human health. Pharmaceuticals and personal care products (PPCPs), antibiotics, and hormones that are used in great demand for health and cosmetic purposes have rapidly culminated in the emergence of environmental pollutants. EPs impact the environment in a variety of ways. EPs originate from animal or human sources, either directly discharged into waterbodies or slowly leached via soils. As a result, water quality will deteriorate, drinking water sources will be contaminated, and health issues will arise. Since drinking water treatment plants rely on water resources, the prevalence of this contamination in aquatic environments, particularly surface water, is a severe problem. The review looks into several related issues on EPs in water environment, including methods in removing EPs. Despite its benefits and downsides, the EPs treatment processes comprise several approaches such as physico-chemical, biological, and advanced oxidation processes. Nonetheless, one of the membrane-based filtration methods, ultrafiltration, is considered as one of the technologies that promises the best micropollutant removal in water. With interesting properties including a moderate operating manner and great selectivity, this treatment approach is more popular than conventional ones. This study presents a comprehensive summary of EP’s existence in the environment, its toxicological consequences on health, and potential removal and treatment strategies.